Attitude, subjective norms, and perceived behavioral control towards fast fashion buying behavior among adults in Klang Valley - Md Jusoh, Zuroni; Loo, Zheng Hao (Malaysian Consumer and Family Economics Association (MACFEA), 2024)
The primary purpose of this study was to determine the correlation between attitude, subjective norms, and perceived behavioral control towards fast fashion buying behavior among adults in Klang Valley, Malaysia. Two hundred eleven adults participated in this study, and volunteers administered the participants. The data were collected through a set of self-administered questionnaires. The finding demonstrated that there is a significant relationship was found between attitude (r=.872, p=.000), subjective norms (r=.771, p=.000), and perceived behavioral control (PBC) (r=.766, p=.000) towards fast fashion buying behavior. Findings from this study suggest that personal factors like attitude, subjective norms, and PBC can significantly correlate with fast fashion buying behavior.